1998
DOI: 10.1046/j.1365-2435.1998.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in the regrowth of Lolium perenne following clipping: effects of nutrients and endophytic fungi

Abstract: 1. The objective of this research was to determine the extent to which regrowth rate after clipping and the specific leaf area (SLA) of genotypes of Lolium perenne were influenced by soil nutrients and endophytic fungi. 2. Twelve infected genotypes were cloned into ramets. Half were treated with a systemic fungicide that greatly reduced endophyte levels; half were untreated and retained high endophyte levels. Ramets of each genotype were subjected to low, medium or high levels of nutrients in a glasshouse for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 42 publications
6
54
0
Order By: Relevance
“…Endophyte infection may alter grasshopper growth performance on some clones but we can not discriminate the effects of endophyte from differences among clones. High variation among clones is not a novel result or contrary to other studies of grassendophyte interactions (Cheplick 1997(Cheplick , 1998. For example, other endophyte studies have shown that resistance levels in perennial ryegrass selections tended to be more variable than those in tall fescue.…”
Section: Clonal Differences Among Host Plantsmentioning
confidence: 57%
See 1 more Smart Citation
“…Endophyte infection may alter grasshopper growth performance on some clones but we can not discriminate the effects of endophyte from differences among clones. High variation among clones is not a novel result or contrary to other studies of grassendophyte interactions (Cheplick 1997(Cheplick , 1998. For example, other endophyte studies have shown that resistance levels in perennial ryegrass selections tended to be more variable than those in tall fescue.…”
Section: Clonal Differences Among Host Plantsmentioning
confidence: 57%
“…Our experimental results with grasshoppers, coupled with the lack of, or unexpected, patterns of endophyte frequency with mammalian herbivory in the natural Arizona fescue populations examined, indicate that endophyte-mediated plant herbivore interactions are probably not the primary selective force shaping the ecology and evolution of endophyte-plant association in this system. Plant genotype has been shown to interact with environmental factors in altering performance of Neotyphodium-infected tall fescue and perennial ryegrass, at least relative to drought tolerance or soil nutrients (Elbersen and West 996;Buck et al 1997;Cheplick 1997Cheplick , 1998. Our experiment was not designed specifically to test plant performance.…”
Section: Clonal Differences Among Host Plantsmentioning
confidence: 99%
“…Endophyte effects can be variable (Cheplick , ; Assuero et al . ), and it is unclear whether E+ and E− history turf cultivars would have differed if all of the E+ history cultivars were high endophyte at seeding.…”
Section: Discussionmentioning
confidence: 99%
“…). Endophyte effects can vary among individuals within a host population (Cheplick , ; Assuero et al . ), and the cultivars commonly used in endophyte‐removal studies may be more strongly affected by endophyte presence than other cultivars (Saikkonen et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to resistance, endophyte infection might influence the tolerance of host plants (Belesky and Fedders, 1996; Cheplick, 1998; Bultman et al, 2004). Tolerance is the degree to which a plant can regrow and reproduce following damage (Strauss and Agrawal, 1999).…”
Section: Discussionmentioning
confidence: 99%